PRAKTIK PENGGUNAAN GARAM BERYODIUM PADA PENDERITA HIPOTIROID DI PUSKESMAS 1 DENPASAR BARAT - Sipahutar, Raja Mahenra Mauliate; Kurniati, Desak Putu Yuli (ARCHIVE OF COMMUNITY HEALTH; Vol 12 No 1 (2025): April 2025, 2025)
ABSTRACT Hypothyroidism is a medical condition that occurs when the thyroid gland does not produce enough thyroid hormone to meet the body's need. This condition is related to the practice of consuming iodized salt in the community. This study aims to determine the practice of using iodized salt in hypothyroid patients at Public Health Center 1 West Denpasar. This research is qualitative with a descriptive approach. Data collection strategy with in-depth interviews and observation with a total of 10 informants. This research was conducted at Public Health Center 1 West Denpasar. The results of this study indicate that informants have knowledge about the use of iodized salt but not good enough knowledge. Most of the informants mentioned getting information from social media. The practice of using iodized salt during food processing in the wrong way by adding iodized salt during the cooking process Informants have a habit of consuming iodized salt with food. However, the frequency of consumption for most of the informants was rare, with a consumption duration of only under 1 year. Iodine deficiency is perceived as harmful to the body. In addition, the distribution of iodized salt regulated by the local government was reported to be poor, so participants had difficulty obtaining iodized salt. Keywords: Hypothyroidism, Iodized Salt, Usage Practice